2015
DOI: 10.1111/jonm.12273
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and leaving intentions of midwives: analysis of a multinational cross-sectional survey

Abstract: Job satisfaction and leaving intentions of midwives: analysis of a multinational cross-sectional surveyAim To investigate the relationship between turnover intentions and job satisfaction among hospital midwives from seven countries and to determine how the related variables differ between countries. Background Studies investigating professional turnover and job satisfaction among midwives are limited in scope. Method A cross-sectional descriptive survey was used to investigate the intended turnover and job sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 27 publications
3
48
0
5
Order By: Relevance
“…Finally, 29 articles were applied to the analysis. Of those 29 articles, 9 were commentaries, reports, or reviews 16-24 ; 10 applied qualitative methods [25][26][27][28][29][30][31][32][33] ; 7 applied quantitative methods 13,14,[34][35][36][37][38] ; and 3 applied a mixed methodology. [39][40][41][42] Ten specifically addressed CNMs/CMs in the United States, and 19 investigated midwives in high-and middleincome countries outside of the United States (see Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, 29 articles were applied to the analysis. Of those 29 articles, 9 were commentaries, reports, or reviews 16-24 ; 10 applied qualitative methods [25][26][27][28][29][30][31][32][33] ; 7 applied quantitative methods 13,14,[34][35][36][37][38] ; and 3 applied a mixed methodology. [39][40][41][42] Ten specifically addressed CNMs/CMs in the United States, and 19 investigated midwives in high-and middleincome countries outside of the United States (see Tables 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…Midwife‐physician collaboration was more prevalent in the literature than collaboration with other members of the health care team; however, that does not demonstrate its hierarchal importance among practice climate attributes. Empirical studies have demonstrated that different elements of the practice climate had differing degrees of importance in different practice settings . For example, Hampton and Peterson found that physician interaction was significantly related to midwives’ job satisfaction only for midwives working in physician offices or hospitals, but among midwives working at educational institutions, the relationship with nurses was predictive of job satisfaction .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet the psychological distress that some midwives endure can impair their cognitive function, decision making skills and their ability to provide compassionate, safe and high quality care (Beaumont, Durkin et al 2016, Knezevic, Milosevic et al 2011). The mental wellbeing of midwives can also be directly correlated with high staff turnovers, high staff sickness rates and low productivity rates, as those in distress can disengage from the profession (Brunetto, Xerri et al 2013, Kenworthy, Kirkham 2011, Jarosova, Gurkova et al 2016). This becomes important as the world tries to recruit and retain a high quality midwifery workforce in the face of global shortages (McInnes, Mc Intosh 2012).…”
Section: Introductionmentioning
confidence: 99%